Enabling safer food in traditional markets - Grace, Delia (Global Alliance for Improved Nutrition, 2022)
Traditional food markets are unique environments where millions of people access nutritious foods every day across the globe. These markets account for the largest distribution share of fresh foods in low- and middle-income countries (LMICs), foods that are essential for improved nutrition outcomes in the communities they serve. At the same time, the health burden of unsafe food is unequally distributed among countries, with the greatest impacts in LMICs. Deeper understanding of traditional markets is essential for risk management of foodborne hazards.